Analisis Kelayakan Usahatani Selada Hidroponik Di Desa Kelorarum Kecamatan Tikung Kabupaten Lamongan - Habibur Rohman; I Made Suparta (Moneter : Jurnal Ekonomi dan Keuangan, 2024)
This research explains the feasibility level of hydroponic lettuce farming in Kelorarum Village, Tikung District, Lamongan Regency. This business is engaged in the production of hydroponic lettuce. This research used a descriptive analysis method which used 6 informants from hydroponic lettuce farming owners as research subjects. Data collected through interviews aims to analyze fixed costs, total costs, variable costs, demand and profits.The feasibility of the business carried out is by using R/C Ratio (Revenue Cost Ratio), B/C Ratio (Benefit Cost Ratio), BEP (Break Even Point) calculations in order to find out whether the business is feasible or not. The results of this research can provide education for business actors regarding the continuation of hydroponic lettuce farming in Kelorarum Village, Tikung District, Lamongan Regency.